Comparison of vacuum ultra-violet emission of Ar/CF4 and Ar/CF3I capacitively coupled plasmas. (18th July 2016) - Zotovich, A; Proshina, O; el Otell, Z; Lopaev, D; Rakhimova, T; Rakhimov, A; de Marneffe, J-F; Baklanov, M R
Abstract: Spectra in the vacuum-ultra violet range (VUV, 30 nm–200 nm) as well as in the ultra-violet(UV) and visible ranges (UV+vis, 200 nm–800 nm) were measured from Ar/CF3 I and Ar/CF4 discharges. The discharges were generated in an industrial 300 mm capacitively coupled plasma source with 27 MHz radio-frequency power. It was seen that the measured spectra were strongly modified. This is mainly due to absorption, especially by CF3 I, and Ar self-trapping along the line of sight, towards the detector and in the plasma itself. The estimated unabsorbed VUV spectra were revealed from the spectra of mixtures with low fluorocarbon gas content by means of normalization with unabsorbed I * emission, at 206 nm, and CF 2 ∗ band ( 1 B1 (0, v′, 0) → 1 A1 (0, v ′ ′, 0)) emission between 230 nm and 430 nm. Absolute fluences of UV CF 2 ∗ emission were derived using hybrid 1-dimensional (1D) particle-in-cell (PIC) Monte-Carlo (MC) model calculations. Absolute calibration of the VUV emission was performed using these calculated values from the model, which has never been done previously for real etch conditions in an industrial chamber. It was seen that the argon resonant lines play a significant role in the VUV spectra. These lines are dominant in the case of etching recipes close to the standard ones. The restored unabsorbed spectra confirm that replacement of conventional CF4 etchant gas with CF3 I in low- k etching recipes leads to an increase in the overall VUV emission intensity. However, emission from Ar exhibited the most intense peaks. Damage to low- k SiCOH glasses by the estimated VUV was calculated for blanket samples with pristine k -value of 2.2. The calculations were then compared with Fourier transform infrared (FTIR) data for samples exposed to the similar experimental conditions in the same reactor. It was shown that Ar emission plays the most significant role in VUV-induced damage.